2023
DOI: 10.1002/adfm.202301794
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Dynamics and Optically Pumped Lasing in 1‐Naphthylmethylamine‐Based Quasi‐2D Perovskite Films

Abstract: Films of the quasi‐2D perovskite based on 1‐naphthylmethylamine (NMA) are promising as the gain medium for optically pumped lasing and future electrically pumped lasing because of its low lasing threshold and small electroluminescence efficiency rolloff. However, reasons for the low threshold and small efficiency rolloff are still unclear. Therefore, exciton dynamics are investigated in NMA‐based quasi‐2D perovskite films. It is found that quenching of bright excitons by other excitons or charge carriers is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…Qin et al realized CW lasing from quasi-2D perovskite films fabricated using NMA or PEA as the B -site large organic cation in air at room temperature, along with excellent laser intensity durability under intense photoexcitation . Especially, NMA-based quasi-2D perovskite films had lower ASE and laser thresholds and very small external quantum efficiency (EQE) roll-off than PEA-based quasi-2D perovskite films did. , Further, we showed that the laser threshold of NMA-based quasi-2D perovskite films was lowered to ∼1 μJ/cm 2 by introducing a circular-shaped DFB resonator . Note that, in NMA-based quasi-2D perovskite films, quenching of bright excitons by other excitons or charge carriers is unlikely, making NMA-based quasi-2D perovskite films a promising candidate for future electrical lasing.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Qin et al realized CW lasing from quasi-2D perovskite films fabricated using NMA or PEA as the B -site large organic cation in air at room temperature, along with excellent laser intensity durability under intense photoexcitation . Especially, NMA-based quasi-2D perovskite films had lower ASE and laser thresholds and very small external quantum efficiency (EQE) roll-off than PEA-based quasi-2D perovskite films did. , Further, we showed that the laser threshold of NMA-based quasi-2D perovskite films was lowered to ∼1 μJ/cm 2 by introducing a circular-shaped DFB resonator . Note that, in NMA-based quasi-2D perovskite films, quenching of bright excitons by other excitons or charge carriers is unlikely, making NMA-based quasi-2D perovskite films a promising candidate for future electrical lasing.…”
Section: Introductionmentioning
confidence: 65%
“…These spectra agree well with the report. 11 SEM and AFM images shown in Figure S2 (Supporting Information) indicated that NMA-based quasi-2D perovskite films had a featureless surface morphology with a small surface roughness R a of ∼0.3 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent follow-up paper, Adachi and co-workers showed that quenching of bright excitons by other excitons or charge carriers does not happen in NMA-based quasi-2D perovskite films and that such films possess shallower defect levels inside the bandgap as compared to PEA-based ones. 24…”
Section: Opportunitiesmentioning
confidence: 99%